Market management and project business development - Smyth, Hedley (Routledge, 2015)
"Market Management and Project Business Development is a guide to the theory and practice of marketing and selling projects in business. Successfully marketing and selling a project to investors is so crucial an element of project management that it dictates whether the project is funded, and as a result, whether it can go ahead. But marketing and promotion are often not part of the competent project manager's skills set. Moreover, most books available are limited to the selling of construction projects, leading to potential "blind spots" in this area for students, specialists and practitioners which have potential to threaten the success of real-life projects on the ground. This book is the first of its kind to provide a set of key principles and guidelines to marketing all types of projects to all types of customers, both B2B and B2C, setting out a range of theoretical developments and applying them throughout to practical scenarios and cases to link theory to practice. Smyth structures his guide through the stages in the process of marketing a project from its inception all the way through to its launch to market, including: the marketing mix, relationship marketing and its project marketing variant, entrepreneurial marketing and the service-dominant logic. This book is valuable reading for all students and specialists in project management, as well as project managers in business, management, the built environment, or indeed any industry"--